Corporate System of Modern Nuclear Knowledge - Arsentyev, Sergey V (Глобальная ядерная безопасность, 2023)
The paper considers methodological issues related to the formation of a corporate system of modern nuclear knowledge, which is the core of the new paradigm of the nuclear industry staffing at the present stage. The category "Personnel/Knowledge" represents the main element which connects the new paradigm of nuclear industry development, which reflects the logic of nuclear sector development, and the new paradigm of management, which, in its turn, reflects the structural changes in the business environment of the XXI century. These two paradigms form the basis of the modern platform for innovative development of the nuclear industry as an informational basis for strategic decision-making. Nuclear personnel support at the present stage, being an integral part of the modern platform, at the same time represents one of the most important and complex tasks of innovative development, the solution of which, being implemented in the corporate strategy.